Adaptation and initial validation of the career resources questionnaire for Portuguese - he students form - Monteiro, Sílvia (2021)
A diversified set of career resources has been related in the literature with career development and career success. The Career Resources Questionnaire (CRQ), based on the Career Success framework, was proposed by Hirschi and colleagues (2018) as an instrument aggregating several constructs that emerged as important predictors of career success. This study aims to examine the psychometric properties of the CRQ to a Portuguese higher education sample, as a way to extend previous evidence of validity presented by the authors of the original version. For such, construct, convergent and discriminant validity were examined. Also, reliability and correlations analysis were conducted, taking some sociodemographic and educational attainment variables. The obtained findings showed adequate results, which support the use of the CRQ in Portugal for research or practical purposes. Suggestions for further research and practical implications are also presented.